Pengembangan Media Pembelajaran Interaktif Sparkol Videoscribe Berbasis Kemampuan Berpikir Kritis Siswa - Syafruddin Syafruddin; Indah Dwi Lestari; Aulia Brigitha (Jurnal Ilmiah Wahana Pendidikan, 2023)
This type of research is Research and Development (R&D), adapted and modified from the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). These stages include preliminary research, design, initial product development, first trial, first product launch, limited field trial, and second product launch. In the early stages of product development, material validation is carried out by lecturers, media validation lecturers and an expert (teacher). Sparkol Videoscribe media was tested on students in two stages, namely the small group test stage with 20 students and the large group test stage with 35 students of class XI MIA 1 SMA Negeri 4 Sumbawa Besar. Data collection techniques using a questionnaire. Data were analyzed descriptively, qualitatively and quantitatively. The research tools used were expert surveys for validation, student answers about product feasibility, and pre- and post-tests about students' critical thinking. Data analysis used qualitative descriptive analysis techniques in the form of expert assessment results and quantitative analysis techniques on students' pre- and post-test results using the SPSS for Windows 21 application. The results showed that 1) the development of a biology learning environment based on the Sparkol videoscript. 2) the results of the feasibility test for material experts obtained an average score of 79.17%, media 80% and practical experts 83.3 in the category highly fulfilling the requirements of biology as a learning tool, and the results of the preliminary exam got an average score of 79.17% Average - average 44, average post-test score 88. 3) Dependent sample The average total score obtained by t-test is 78, indicating that the Sparkol writing-based learning environment is very effective. Biology learning tools to develop students' critical thinking.